“Grammar” of verbal image in Russian literature in teaching foreigners - E. Eremina (Rhema. Рема, 2020)
Verbal images are immanent for fiction texts. Many features of verbal images are difficult to understand for foreigners. The paper considers grammatical structure of verbal images as a source of a possible perceptive failure. Strategies for foreign students to overcome difficulties in understanding lexical, grammatical and imagery structure of the text are described. Experimental data on the perception of “grammar” of verbal images by foreign students is provided. Activities for developing skills in comprehension ‘grammar’ of verbal images for intermediate students are suggested. Verbal images of the poem “Birch” by S.A. Esenin are analyzed as an example.